CREAM: 70 days of flight from 2 launches in Antarctica - T. J. Brandt; A. Barrau; S. W. Nam; Inkyu Park; S. P. Swordy; Riccardo Zei; S. L. Nutter; J. A. Jeon; Arturo Alejandro Menchaca-Rocha; M. H. Lee; L. Derome; H. S. Ahn; et al. (Advances in Space Research, 2008)
The Cosmic-Ray Energetics And Mass balloon-borne experiment has been launched twice in Antarctica, first in December 2004 and again in December 2005. It circumnavigated the South Pole three times during the first flight, which set a flight duration record of 42 days. A cumulative duration of 70 days within 13 months was achieved when the second flight completed 28 days during two circumnavigations of the Pole on 13 January 2006. Both the science instrument and support systems functioned extremely well, and a total 117 GB of data including 67 million science events were collected during these two flights. Preliminary analysis indicates that the data extend well above 100 TeV and follow reasonable power laws. The payload recovered from the first flight has been refurbished for the third flight in 2007, whereas the payload from the second flight is being refurbished to be ready for the fourth flight in 2008. Each flight will extend the reach of precise cosmic-ray composition measurements to energies not previously possible.